The fundamentals of counterterrorism law - Zusman, Lynne K. (Section of Administrative Law and Regulatory Practice, American Bar Association, 2014)
This book dives into the basic legal framework surrounding the many aspects of terrorism, covering such critical topics as international investigations, national security law, ethics, privitization, drones, cyberterrorism and much more.